Exploring the Mechanisms of Exercise-Induced Hypoalgesia Using Somatosensory and Laser Evoked Potentials - Jones, Matthew D.; Taylor, Janet L.; Booth, John; Barry, Benjamin K. (Frontiers in Physiology, 2016)
Exercise-induced hypoalgesia is well described, but the underlying mechanisms are unclear. The aim of this study was to examine the effect of exercise on somatosensory evoked potentials, laser evoked potentials, pressure pain thresholds and heat pain thresholds. These were recorded before and after 3-min of isometric elbow flexion exercise at 40% of the participant’s maximal voluntary force, or an equivalent period of rest. Exercise-induced hypoalgesia was confirmed in two experiments (Experiment 1 – SEPs; Experiment 2 – LEPs) by increased pressure pain thresholds at biceps brachii (24.3% and 20.6% increase in Experiment 1 and 2, respectively; both d > 0.84 and p < 0.001) and first dorsal interosseous (18.8% and 21.5% increase in Experiment 1 and 2, respectively; both d > 0.57 and p < 0.001). In contrast, heat pain thresholds were not significantly different after exercise (forearm: 10.8% increase, d = 0.35, p = 0.10; hand: 3.6% increase, d = 0.06, p = 0.74). Contrasting effects of exercise on the amplitude of laser evoked potentials (14.6% decrease, d = -0.42, p = 0.004) and somatosensory evoked potentials (10.9% increase, d = -0.02, p = 1.72) were also observed, while an equivalent period of rest showed similar habituation (laser evoked potential: 7.3% decrease, d = -0.25, p = 0.14; somatosensory evoked potential: 20.7% decrease, d = -0.32, p = 0.006). The differential response of pressure pain thresholds and heat pain thresholds to exercise is consistent with relative insensitivity of thermal nociception to the acute hypoalgesic effects of exercise. Conflicting effects of exercise on somatosensory evoked potentials and laser evoked potentials were observed. This may reflect non-nociceptive contributions to the somatosensory evoked potential, but could also indicate that peripheral nociceptors contribute to exercise-induced hypoalgesia.